(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
This paper explores the complex relationships between environmental factors and age-related health outcomes by examining how different stages of life affect susceptibility to environmental risks. Factors such as environmental pollution, climate changeability and lifestyle choices can have a significant impact on the human body, which can have different effects depending on age. By analysing the correlation between environmental exposure and age-related changes in physiology and vulnerability to disease, this study aims to fully understand how individuals at different stages of life are exposed to the environment.